2006
DOI: 10.1002/jgt.20210
|View full text |Cite
|
Sign up to set email alerts
|

A degree sum condition for longest cycles in 3‐connected graphs

Abstract: Abstract:For a graph G, we denote by d G (x) and κ(G) the degree of a vertex x in G and the connectivity of G, respectively. In this article, we show that if G is a 3-connected graph of order n such thatfor every independent set {x, y, z}, then G contains a cycle of length at least min{d − κ(G), n}.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…On the other hand, one often try to find a dominating cycle in order to find a Hamilton cycle in a given graph (recall that a cycle C in a graph G is dominating if every edge of G is incident with a vertex of C). For example, if some longest cycle in a graph G is dominating and the independence number of G is at most its minimum degree, then G has a Hamilton cycle (the related results can be found in [4,24]). It is also shown that the dominating cycle conjecture that "every cyclically 4-edge-connected cubic graph has a dominating cycle" by Fleischner [13] is equivalent to not only the well-known conjecture that "every 4-connected K 1,3 -free graph is…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, one often try to find a dominating cycle in order to find a Hamilton cycle in a given graph (recall that a cycle C in a graph G is dominating if every edge of G is incident with a vertex of C). For example, if some longest cycle in a graph G is dominating and the independence number of G is at most its minimum degree, then G has a Hamilton cycle (the related results can be found in [4,24]). It is also shown that the dominating cycle conjecture that "every cyclically 4-edge-connected cubic graph has a dominating cycle" by Fleischner [13] is equivalent to not only the well-known conjecture that "every 4-connected K 1,3 -free graph is…”
Section: Introductionmentioning
confidence: 99%